Unveiling The Bandura’s Theory On Self- Efficacy: Listening To The Voices Of The Married Students - CAMBRI, BEVERLY GAY N. (The journal of contemporary issues in business and government, 2021)
This study unveils the Bandura’s Theory on Self-efficacy on the lived-experiences of married students in the private universities. This study posited to explain the inner voices of the married students when they felt difficulties as they journey academically. The researcher made use of the descriptive correlational design and interview methods to examine the influential factors on the academic performance among married college students in different private universities and colleges in Tuguegarao City. There were seventy-seven married students participated in the study. Based on the result of the study, there was a high self-efficacy among married students as they performed very well in their academic task while taking care of their family. These married students were already prone of multitasking and successfully sent requirements academically while taking care of their family. Therefore, universities may provide counseling programs and conduct seminars that would assist these married students a well- balance way of life